2017
DOI: 10.1063/1.4973576
|View full text |Cite
|
Sign up to set email alerts
|

KSbOSiO4 microcrystallites as a source of corrosion of blue-green lead-potassium glass beads of the 19th century

Abstract: KSbOSiO 4 microcrystallites as a source of corrosion of blue-green lead-potassium glass beads of the 19th century Presently, deterioration of glass beads is a significant problem in conservation and restoration of beaded exhibits in museums. Glass corrosion affects nearly all kinds of beads but cloudy blue-green ones are more than others subjected to disastrous destruction. However, physical and chemical mechanisms of this phenomenon have not been understood thus far. This article presents results of a study o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…FTIR spectra of the turquoise glass seed beads at different stages of deterioration [13,15] are presented in figure 4. A strong and wide band in the region from 820 to 1250 cm −1 and weak bands in region from 650 to 820 cm −1 are observed in all spectra.…”
Section: Micro-ftir Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…FTIR spectra of the turquoise glass seed beads at different stages of deterioration [13,15] are presented in figure 4. A strong and wide band in the region from 820 to 1250 cm −1 and weak bands in region from 650 to 820 cm −1 are observed in all spectra.…”
Section: Micro-ftir Spectroscopymentioning
confidence: 99%
“…In the previous works, we established that formation of micro and nanocrystallites of orthorhombic KSbOSiO 4 (KSS) in glass matrix (figures 2(e)-(g)), which arise during glass melting and bubbling, 4 is one of the main causes of deteriorating of turquoise glass seed beads [7,8,15,14,16]. We concluded that KSS precipitates and their clusters gave rise to internal stress (likely, tension) causing strain (likely, tensile one) in the glass bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). However, the results of the previous studies show the absence of sulfur and the presence of lead in similar beads.…”
Section: Resultsmentioning
confidence: 99%
“…The X‐ray fluorescence study of the 19th‐century cloudy blue‐green beads shows that the beads are made of lead–potassium glass, and light scattering spectroscopy demonstrates the presence of microscopic inhomogeneities on the cleavage surfaces of fragmented beads . Scanning electron microscopy, X‐ray energy‐dispersive spectroscopy microanalysis, and X‐ray diffractometry make it possible to identify inhomogeneities as orthorhombic KSbOSiO 4 (KSS) crystals . Such crystals often form relatively large clusters with sizes ranging from several hundreds of nanometers to several tens of micrometers.…”
Section: Introductionmentioning
confidence: 99%